Management of Gap Nonunion Tibia by Ilizarov Ring Frame: Zamir Soomro, Zulfiqar Soomro, Azizullah, Rashid Muhammad, Saeed Samo (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To determine the effectiveness of Ilizarov circular frame in the management of gap nonunion of tibia.Methods: This is descriptive study conducted from July 2008 to May 2015. Patients of either gender with age ranging from 15 to 65 years, having nonunion (clean and infected nonunion) in tibia with defect of 3.5 to 18cm due to trauma or firearm injury were included. Outcome was assessed using ASAMI (Association for the Study and Application of the Methods of Ilizarov) criteria.Results: 46 patients were included in this study. Outcome was observed on the basis of radiographs and clinical assessments. On the basis of radiographs 26 (56.52%) patients showed excellent response, 14 (30.43%) patients showed good response and, 4 (08.69%) patients showed fair response and in 2 (04.34%) patients showed poor response. On the clinical assessment response was excellent in 18 patients (39.13%), good in 22 patients (47.82%), fair in 4 (08.69%) patients and poor in 2 patients (04.34%).Conclusion: Ilizarov ring fixator is excellent and useful in the treatment of gap nonunion of tibia for intercalary bone transport. Bone transport by Ilizarov was found good with consolidation due to early full weight bearing, but it needs adequate preplanning, patientâ€™s selection and proper postoperative management.